Efficacy of non-pharmacological interventions on sleep quality in patients with cancer-related insomnia: a network meta-analysis - Luo, Yu; He, Hua; Cao, Caihong; Xu, Ruoxin; Tian, Xiaohua; Jiang, Gufen (Frontiers in Neurology, 2024)
Objective Despite the widespread application of non-pharmacological therapies in treating cancer-related insomnia, a comprehensive assessment of these methods is lacking. This study aims to compare the efficacy of 11 non-pharmacological interventions for cancer-related insomnia, providing a theoretical basis for clinicians in choosing treatment methods. Methods We searched five databases, including the Cochrane Central Register of Controlled Trials, PubMed, Embase, Wiley Library, and Web of Science, for relevant randomized controlled trials. Included studies involved patients diagnosed with cancer-related insomnia, employed non-pharmacological treatments, and reported outcomes using the PSQI and ISI. Bayesian statistical methods were used for the network meta-analysis, and statistical processing was performed using Review Manager 5.4 and Stata 14.0 software. The results were thoroughly analyzed and evaluated, and publication bias was assessed using funnel plot tests. Results Our study included 41 randomized controlled trials, comprising 11 different non-pharmacological interventions (3,541 participants), the network analysis identifying Electroacupuncture as the most effective, with a SUCRA value of 92.2% in ISI, this was followed by Professionally administered Cognitive behavioral therapy for insomnia(PCBT-I) and Mindfulness-based cognitive therapy(MBCT), with SUCRA values of 78.4 and 64.1%, respectively. Traditional Cognitive behavioral therapy for insomnia(CBT-I) and VCBT-I showed lower efficacy with SUCRA values of 55.9 and 55.2%, respectively. Exercise interventions and control groups had the lowest efficacy, with SUCRA values of 24.0 and 16.1%. Using PSQI as the outcome measure, Massage therapy ranked highest in improving sleep quality with a SUCRA value of 92.2%, followed by Professionally administered Cognitive behavioral therapy for insomnia (PCBT-I) and Electroacupuncture. League tables indicated significant improvements in sleep outcomes for Electroacupuncture and MT compared to control groups, with Electroacupuncture (EA) showing an MD of −7.80 (95% CI: −14.45, −1.15) and MT an MD of −4.23 (CI: −8.00, −0.46). Conclusion Considering both outcome indicators, Electroacupuncture was significantly effective in alleviating the severity of insomnia, while MT was most effective in improving sleep quality. Therefore, in the non-pharmacological interventions for cancer-related insomnia, Electroacupuncture and MT May be particularly effective choices. Future research should further explore the specific mechanisms of action of these interventions and their efficacy in different patient groups.